Long-term evaluation of the distal transverse plantar approach for Morton’s neuroma excision (Swiss Medical Weekly, 2020)
BACKGROUND There is currently no consensus on the ideal approach for the operative treatment of Morton’s neuroma. The distal transverse plantar approach aims at optimal exposure without the scar complications associated with the longitudinal plantar approach. Long-term evaluation based on validated outcome instruments is lacking. The main purpose of this retrospective study was to evaluate the long-term clinical outcome of this approach using validated function and scar evaluation scores. METHODS Forty-nine patients operated on at our institution were examined clinically by two independent observers using the Foot and Ankle Ability Measure (FAAM) and the Vancouver Scar Scale (VSS). Patients who underwent neurectomy alone and those who had additional foot surgery were compared. RESULTS Assessment at a mean of 7.9 years (range 4–12) postoperatively revealed a mean FAAM score of 84.8 ± 25% and a mean VSS score of 1.57 ± 1.7. Patients who underwent neurectomy alone had higher FAAM scores at follow up. We observed no complication that required an additional procedure. CONCLUSIONS The transverse plantar approach results in good objective outcome scores, including scar healing, in the long term. This is our preferred technique because, in our experience, it offers optimal visualisation of the nerve, does not require deep dissection and allows the exposure of two adjacent web spaces of the foot through a single incision.